Approximation of Holomorphic Mappings on Infinite Dimensional Spaces - Calıskan, Erhan (Revista Matemática Complutense, 2004)
In this article we examine necessary and sufficient conditions for the predual of the space of holomorphic mappings of bounded type, Gb(U), to have the approximation property and the compact approximation property and we consider when the predual of the space of holomorphic mappings, G(U), has the compact approximation property. We obtain also similar results for the preduals of spaces of m-homogeneous polynomials, Q(mE).